Arp2/3 complex controls T cell homeostasis by maintaining surface TCR levels via regulating TCR+ endosome trafficking - Ye Zhang; Hao Shen; Haifeng Liu; Haiyun Feng; Yan Liu; Xiaoyan Zhu; Xiaolong Liu (Scientific Reports, 2017)
Abstract T cell receptor (TCR) signaling is important for T cell homeostasis and function. However, how surface TCR levels are regulated and its biological significance on T cells remains largely unknown. Here, we show that the T cell-specific deletion of Arpc2, a component of Arp2/3 complex, results in compromised peripheral T cell homeostasis. Arp2/3 complex-nucleated actin filaments are essential for maintaining surface TCR levels by regulating TCR+ endosome trafficking in resting state and controlling polarization of TCR+ endosomes during immune synapse formation in T cells. Additionally, Arpc2-TKO T cells are unable to form immune synapse. Interestingly, defected T cell homeostasis is caused by reduced surface TCR levels but not impaired immune synapse formation. Collectively, our findings suggest that Arp2/3 complex-nucleated actin filaments are required for maintaining surface TCR levels via regulating TCR+ endosome trafficking which is essential for T cell homeostasis.